Dendrocalamus atroviridis (Poaceae: Bambusoideae, Bambuseae), a new species from Southwest China - Yang, Han-Qi; Xie, Ning; Sun, Mao-Sheng; Xu, Tian; Li, De-Zhu (Phytotaxa, 2016)
Dendrocalamus atroviridis, a new species from southern Yunnan, China, is described and illustrated. It resembles Dendrocalamus brandisii, but is characterized by dark-green culms, longer internodes, culm sheaths covered with densely brown bristles, erect blade of the culm sheath, 5–15 pseudospikelets at each node of the flowering branches, smaller pseudospikelets, as well as longer anthers and styles. It is only known from Menghai County, in Yunnan, China.